Pola Kausalitas Nilai Tukar Rupiah Dan Ekspor Kopi Indonesia Ke Amerika Serikat - Kinasih, Dinda Retno; Fisabilillah, Ladi Wajuba Perdini (Independent: Journal of Economics, 2023)
One of the agricultural product that play a part in the business is coffee. The purpose of this research is to find out the causal relationship between the rupiah exchange rate and the export of Indonesian coffee to the United States on 2000-2021. The quantitative method is the method used by the researchers in this research. The analytical technique used is the Granger causality test. In the results of this research, one-way causality was obtained on the coffee export variable affecting the rupiah exchange rate but an inverse causality was not found in the rupiah exchange rate variable on coffee exports. Keywords: Coffee, Exports, Exchange Rate, Granger Causality